PERBANDINGAN EFEKTIVITAS PENURUNAN TEKANAN DARAH DENGAN PEMBERIAN KOMBINASI AMLODIPIN DENGAN KAPTOPRIL DAN AMLODIPIN DENGAN LISINOPRIL PADA PASIEN HIPERTENSI DI RUMAH SAKIT PKU MUHAMMADIYAH MAYONG JEPARA - Endang Setyowati; Ezara Mila Fawwazah Prayitno; Yayuk Mundriyastutik; Ratna Dewi Isnaeni (Universitas Muhammadiyah Kudus, 2021)
Hypertension is a non-communicable disease as well as one of the mortality factors in the world with a prevalence of 22% of the world's population. According to riskesdas, the prevalence of hypertension in Indonesia increased by 8.3% and 8.2% per year 2018. The selection and treatment of hypertension also requires the use of effective drugs and can provide good tolerance. The effectiveness as well as the benefits in the treatment of hypertension race on the measurement of blood pressure that has reached the target. The drop in blood pressure can also be influenced by the rational use of drugs both monotherapy and in combination. The purpose of this study was to analyze the comparison of the effectiveness of the use of drugs combination of amlodipine with captopril and amlodipine with lysinopril. This research method includes qualitative research using the cross sectional method with a retrospective approach. The results of the independent t-test of the significance value of the systolic category are 0.7810.05 and the significance value of the diastolic category is 0.9230.05. Pacidists who received combination therapy of amlodipine-captopril and amlodipine-lisinopril who achieved the targetse number of 43 patients. After independent t-test before and after therapy, it can be concluded that both the systolic category and the diastolic category regarding the effectiveness of the two combinations have no significant differences and the amlodipine-lysinopril combination is more effective in achieving the target of lowering blood pressure than amlodipine-captopril